2021
DOI: 10.1002/cncr.33794
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use among cancer survivors in the United States: Analysis of a nationally representative sample

Abstract: Background Research on cannabis use among those with a history of cancer is limited. Methods Prevalence of past‐year cannabis use among individuals with and without a cancer history and predictors of use within these 2 groups were determined using data from the Population Assessment of Tobacco and Health study, a nationally representative, longitudinal survey conducted in the United States (waves 1‐4; 2013‐2018). Discrete time survival analyses were used to estimate baseline (wave 1) predictors (physical healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
(54 reference statements)
3
19
0
Order By: Relevance
“…The cited study, in fact, observed a 16% cannabis prevalence, and among the 16% of users, 56%—9% overall—reported using cannabis in the past 30 days 4 . Indeed, with prior studies reporting prevalence estimates ranging from 8% to 24%, the results of the current report are nearly double the upper range of any prior study among general oncology patients 5‐10 or patients diagnosed with cancers at specific anatomic sites 4,11,12 . To our knowledge, only Pergam et al 8 have reported on cannabis use among patients with breast cancer at a single cancer center in Seattle, Washington, where adult medical and nonmedical cannabis use is legal.…”
mentioning
confidence: 45%
“…The cited study, in fact, observed a 16% cannabis prevalence, and among the 16% of users, 56%—9% overall—reported using cannabis in the past 30 days 4 . Indeed, with prior studies reporting prevalence estimates ranging from 8% to 24%, the results of the current report are nearly double the upper range of any prior study among general oncology patients 5‐10 or patients diagnosed with cancers at specific anatomic sites 4,11,12 . To our knowledge, only Pergam et al 8 have reported on cannabis use among patients with breast cancer at a single cancer center in Seattle, Washington, where adult medical and nonmedical cannabis use is legal.…”
mentioning
confidence: 45%
“…The prevalence of pain among this population was as high as 55% during anticancer treatment . National studies have revealed important age differences in marijuana use among cancer survivors, finding younger survivors more likely to report past or recent marijuana use, greater accessibility, and lower perceived risks associated with marijuana compared with their counterparts without cancer . By focusing on adult patients younger than age 65 years receiving cancer treatment, we sought to shed light on the implications of medical marijuana legalization for a population that has elevated needs for cancer pain management but also is potentially more likely to use medical marijuana.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Several cross-sectional surveys have linked cannabis use among cancer survivors to the presence of pain. (11,12) In addition, prior work among cancer survivors, has associated characteristics such as male sex, lack of insurance, younger age and lower education to cannabis use. (3,11) One study found that those with cancer who use cannabis are more likely to have chronic pain that impacts their daily activities (high impact chronic pain).…”
Section: Introductionmentioning
confidence: 99%